Kinerja Usahatani Perkebunan Kakao Monokultur dan Polikultur di Kecamatan Gedong Tataan Kabupaten Pesawaran Provinsi Lampung - Dewi Mulia Sari; Wan Abbas Zakaria; Lidya Sari Mas Indah; Yuliana Saleh; Amanda Putra Seta (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
Cocoa is one of the leading plantation commodities in Lampung Province.  This commodity has contributed high export value in raw form and has become the main raw material in various agro-industries.  The main cocoa production center in Lampung Province is Pesawaran. All cocoa plantations in Pesawaran Regency are smallholder plantations.  Smallholder plantations have an important and strategic role, especially in increasing income and providing employment for the community.  There are two research objectives.  First, to analyze the performance level of monoculture and polyculture cocoa plantations in Gedong Tataan Sub-district, Pesawaran Regency, Lampung Province.  Secondly, to analyze the difference on the profit levels of cocoa plantations with monoculture and polyculture in Gedong Tataan Subdistrict, Pesawaran Regency, Lampung Province.  The research location was selected purposively by the consideration that Sungai Langka Village is the main cocoa bean producer in Gedong Tataan Subdistrict, Pesawaran Regency. The research was conducted by a survey method, in which samples of 34 cocoa farmers were chosen by simple random sampling technique. The results showed that R/C ratio on total costs obtained by cocoa farmers with monoculture cropping pattern is 2.97. Meanwhile, the highest level of R/C ratio on total costs of polyculture is the cocoa-coffee-durian cropping pattern (3.69).  There was no significant difference between performance of monoculture and on polyculture cocoa plantations. Key words: cocoa, monoculture, polyculture, performance